Serum Metabonomic Study of Patients With Acute Coronary Syndrome Using Ultra-Performance Liquid Chromatography Orbitrap Mass Spectrometer - Song, Lei; Zhang, Zhongxiao; Qiu, Zhaohui; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2021)
Acute coronary syndrome (ACS) can cause arrhythmia, heart failure and even sudden death. The aim of this study was to identify potential metabolic biomarkers in patients with ACS. Serum metabonomics based on Ultra-performance liquid chromatography/Orbitrap MS was used to analyze the serum samples from 45 ACS patients and 29 healthy controls. Multivariate statistical analysis were used to screen the biomarker of ACS. 69 biomarkers were identified enriched in 19 metabolic pathways, 43 biomarkers were increased significantly and 26 biomarkers were down-regulated significantly in ACS group. The main class of them were lyso-SM, cinnamic acids, cholines and primary amides. The ROC analysis showed the LysoPC(20:4(8Z,11Z,14Z,17Z)/0:0), SM(d18:0/16:0) and SM(d18:1/14:0) showed high diagnostic ability for ACS with the AUC value of 0.936,0.932 and 0.923 respectively. and the AUC value of the diagnostic model constructed with the 5 combined biomakers were 0.96. Therefore, these biomarkers may improve the diagnosis efficacy of ACS. This study also implied that Glycerophospholipid metabolism, Biosynthesis of unsaturated fatty acids, Linoleic acid metabolism，Valine, leucine and isoleucine biosynthesis played important roles in ACS. Network analysis by IPA showed these biomarkers were correlated to the cardiac hypertrophy signaling pathway. These findings will help to improve the ability of accurate diagnosis and intervention of acute coronary syndrome.